Dispersion hardening of an AlSi3Mg alloy with Cr and Mn addition. (2019) - Tocci, Marialaura; Pola, Annalisa; Angella, Giuliano; Donnini, Riccardo; Vecchia, Giovina Marina La
Abstract: The effect of solution treatment on an AlSi3Mg alloy with and without Cr and Mn addition was investigated. Beside the modification of the morphology of Fe-containing intermetallics, Cr and Mn allowed the formation of dispersoids in the aluminium matrix after solution heat treatment, as shown by scanning transmission electron microscope (STEM) observations. These particles were responsible of enhanced Vickers microhardness of the aluminium matrix in comparison with the base alloy due to dispersion hardening mechanism. Furthermore, a slow heating rate enhanced uniform distribution of dispersoids, as shown by STEM observation, and it leaded to an increase in the material hardness